Cross Sector Risk Management Analysis on Public-Private Partnership, Case Study Drinking Water Supply System (SPAM) Jatiluhur I - Praja, Adhadi; Santoso, Sugeng (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aim to analyzes cross-sector risk management based on ISO 31000 in the Jatiluhur I SPAM PPP project. Using qualitative methods, data was collected through interviews and focus group discussions. The results showed that the principle of risk management needs to adopt collaborative as an addition, which show intergation, coordination, synergy and synchronization for all entities involved to achieve national development goals. Emphasizing functions and responsibilities of 3 lines in the design of the risk management framework. Risk assesement was conducted and there were 20 risks identified: 1 strategic, 11 operational, 3 policy and 5 financial risks. This research contributes significantly to the integration and effectiveness of national project risk management.